Endovascular Management of Intracranial Dural AVFs: Transvenous Approach - Bhatia, K.D.; Lee, H.; Kortman, H.; Klostranec, J.; Guest, W.; Wälchli, T.; Radovanovic, I.; Krings, T.; Pereira, V.M. (American Journal of Neuroradiology, 2022)
SUMMARY: In this third review article on the endovascular management of intracranial dural AVFs, we discuss transvenous embolization approaches. Transvenous embolization is increasingly popular and now the first-line approach for ventral dural AVFs involving the cavernous sinus and hypoglossal canal. In addition, transvenous embolization is increasingly used in lateral epidural dural AVFs in high-risk locations such as the petrous and ethmoid regions. The advantage of transvenous embolization in these locations is the ability to retrogradely embolize the draining vein and fistula while reducing the risk of ischemic cranial neuropathy or brain parenchymal infarction commonly feared from a transarterial approach. By means of coils ± ethylene-vinyl alcohol copolymer, transvenous embolization can achieve angiographic cure rates of 80%–90% in ventral locations. Potential complications include transient cranial neuropathy, neurologic deterioration due to venous outflow obstruction, and perforation while navigating pial veins. Transvenous embolization should be considered when dural AVFs arise in proximity to the vasa nervosum or extracranial-intracranial anastomoses.CCFcarotid cavernous fistuladAVFdural AVFECAexternal carotid arteryEC-ICexternal carotid to internal carotidEVOHethylene-vinyl alcohol copolymerIPSinferior petrosal sinusJR-NET3Japanese Registry of Neuro Endovascular TherapyRPCreverse pressure cookerTAEtransarterial embolizationTVEtransvenous embolization